Littoral cell angioma of the spleen in a child with Cornelia De Lange syndrome - Naeem Liaqat; Areej Abdullatif Madani; Nadeem Kausar; Mohammed Othman Abdulrahman Almaimani; Anies Mahomed (Elsevier, 2021)
Littoral Cell Angioma (LCA) is a benign and rare vascular tumor of the spleen. It is uncommon in children, and a comprehensive literature review has yielded only 12 published pediatric cases of LCA. Here we present a seven year old, female who was a known case of Cornelia De Lange syndrome who presented with splenic cysts and underwent splenectomy. Histopathological review revealed LCA.